How the twins grew up : a collection of short stories for children = Makurire akaita mapatya : muunganidzwa wengano dzevana vadiki - Đuričković, Milutin, 1967- (Mwanaka Media and Publishing Pvt Ltd, 2018)
This English/Shona edition of How the Twins Grew Up brings authentic biographical stories of two twin brothers. The stories take place in their family circle, at school, at home or in the backyard. It is written as a realistic prose narrative with a humorous intonation, unexpected dramatic twists and interesting punch lines. The stories are short and concise, with effective endings and situations, full of laughter, caricature and absurdity. The book has been translated into 20 languages and has received several awards. For those who love humour and want to return to their childhood, these stories will come as a real refreshment and a unique artistic experience.